Effect of Planting Time and Phosphorus Dosage on Growth, Yield and Quality Attributes of Indian bean (Lablab Purpureus L.) - Kharbamon, B.; Jha, A. K.; Verma, V. K.; Choudhury, B. U.; Deka, Bidyut C. (Indian Journal of Hill Farming, 2016)
Indian bean is one of the most important leguminous vegetable crops grown widely in the North Eastern Region of India. The crop is having great demand in the region and it is grown for tender pods as vegetable and seeds as pulse. To ensure the availability of vegetables during off- season with higher yield an experiment was conducted to study the response of semi-dwarf photo-insensitive line of dolichos bean (RCDL-10) to time of planting (May, June, July, August, September and October) and graded dosage of phosphorus (30, 40, 50 and 60 kg/ha P2O5) for growth, flowering behaviour, yield and quality traits. Longest vine (331.16 cm) and highest number of primary branches (15.31) were recorded in the July sowing whereas, shortest vine length (158.66 cm) and lowest number of branches per plant was recorded in October sowing (10.08). May sowing took the least number of days to complete the physiological and developmental stages. May planting gave the highest yield (168.70 g/plant) and yield attributes as well as highest crude protein (25.3%) content of the pods. Similarly, phosphorus dose of 60 kg/ha recorded the highest plant growth, number of flowers per panicle (9.41), yield (123.04 g/plant) and maximum crude protein content (25.22 %) of the pods as compared to the lower dosage. Hence, photo-insensitive line RCDL-10 can be cultivated as an off season crop during may having higher yield with the application of 60kg P2O5.